UV Curing of Perfluoropolyether Oligomers Containing Graphene Nanosheets to Enhance Water‐Vapor Barrier Properties. Issue 16 (14th July 2014) - Vitale, Alessandra; Merlo, Simone; Rizza, Giancarlo; Melilli, Giuseppe; Sangermano, Marco
<x xml:space="preserve">Abstract</x> Recently, graphene and its derivative nanosheets have been considered as potential candidates for gas barrier membranes. Here, the effect on the water‐vapor barrier properties of incorporating graphene nanoplatelets into a UV‐curable perfluoropolyether methacrylic oligomer is investigated. By combining the hydrophobicity of the highly fluorinated polymer with the tortuous path induced by the graphene sheets, the barrier properties of the crosslinked films are further enhanced, acting both on the thermodynamic (low solubility) and kinetic (longer diffusion path) contribution of the water‐vapor diffusion through the polymeric films. Good performance in increasing water‐vapor barrier properties at a very low filler loading is obtained: the permeability is halved in the presence of only 0.3 wt% graphene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>